Low circulation of respiratory syncytial and influenza viruses during autumn-winter 2021 in the industrial workplace and long-term healthcare facilities in Athens, Greece - Papachristou, Eleni; Rokka, Chrysoula; Sotiriadou, Triantafyllia; Maneka, Leukothea; Vassilakis, Alexandros; Sapounas, Spyros; Paraskevis, Dimitrios; Jahaj, Eddison; Kotanidou, Anastasia; Lagiou, Pagona; Magiorkinis, Gkikas (Frontiers in Medicine, 2023)
The emergence of SARS-CoV-2 has pinpointed the importance of non-pharmaceutical interventions (NPIs), which have been traditionally used for the prevention of the spread of respiratory viruses among individuals. The aim of our study was to capture the level of circulation of respiratory syncytial and influenza viruses during a period of medium severity NPIs due to SARS-CoV-2 pandemics in Greece. A total of 2,225 nasopharyngeal samples were received during the year 2021 as a part of the routine diagnostic service and were divided into two study groups: (a) January to September 2021 and (b) October to the end of December 2021. The latter is the time of the year when there is a peak of infections from most respiratory viruses, and thus, most of the samples were tested in that period. The samples were taken from three different sites, i.e., (a) industrial workers in a factory, (b) elderly homecare facilities, and c) people who actively asked to be tested for SARS-CoV-2. All the samples were tested simultaneously for SARS-CoV2, RSV, and influenza virus. A total of 2,110 samples were negative for either of the three viruses, 106 were SARS-CoV-2-positive, and 9 were RSV-positive from which 7 were found in the workers’ group. None of the samples was found to be positive for the influenza virus, and no sample had co-infection. Our study shows the low-level circulation of RSV and influenza viruses during autumn-winter 2021 and will provide a reference for future studies of RSV and influenza in Greece.